2017
DOI: 10.1186/s13321-017-0216-0
|View full text |Cite
|
Sign up to set email alerts
|

Searching for bioactive conformations of drug-like ligands with current force fields: how good are we?

Abstract: Drug-like ligands obtained from protein–ligand complexes deposited in the Protein Databank were subjected to conformational searching using various force fields and solvation settings. For each ligand, the resulting conformer pool was examined for the presence of the bioactive (crystal pose-like) conformation. Similarity of conformers toward the crystal-pose was quantified as the best achievable root mean squared deviation (RMSD, heavy atoms only). Analyzing the conformer pools generated by various force field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Such conformer generation is recommended subsequent to creating an initial threedimensional geometry if desired. [36,38,39,40,41,42,43,44,45]…”
Section: Resultsmentioning
confidence: 99%
“…Such conformer generation is recommended subsequent to creating an initial threedimensional geometry if desired. [36,38,39,40,41,42,43,44,45]…”
Section: Resultsmentioning
confidence: 99%
“…Such conformer generation is recommended subsequent to creating an initial threedimensional geometry if desired. [36,38,39,40,41,42,43,44,45]…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the ideal docking protocol would include all (or a set of most representative) peptides with high affinities for the targeted HLA-variant to ensure experimental success, but in the absence of fully solved HLA-peptide binding modes, this will be a difficult challenge to solve. A recent study by Gürsoy and Smieško [ 96 ] tested the reliability of force fields to accurately predict biologically active conformations of drugs, and revealed that conformational accuracy of a force field decreases as the number of rotatable bonds in a compound increases. Obviously, accurately predicting the binding conformation of peptides will be a major obstacle due to the high number of rotatable bonds, despite some significant progress [ 88 ].…”
Section: Resultsmentioning
confidence: 99%